Consumer Perception on Quality of Bakpao Telo with Importance – Performance Analysis Method - Santoso, Imam; Mulyarto, Aunur Rofiq; Maharani, Sukma (Jurnal Teknologi Pertanian, 2011)
Consumer perception on food quality is a key factor for success in food industri development.  Many factors influence consumer perception on food quality. The purpose of this research was to identify the attributes of food product and evaluate it’s performance to find out attributes based on consumer perception. The respondent in this research was the consumer that bought and consumed bakpao telo in Sentra Pengembangan Agribisnis Terpadu (SPAT). The sampling technique used accidental sampling with a number of sample is 75 people, based on linier time function. The analysis of data used Importance–Performance Analysis. The result of this research showed that shape of product, quality of service, advertisement and promotion, and expired date of the product, registered in Departemen Kesehatan, halal guarantee, texture of bakpao, flavor variation of product, flavour of product, guarantee of safety product  and nutrition were the key atributes of bakpao telo quality.Keywords: perception, bakpao telo, importance–performance analysis